Validating molecular diagnostic protocols for cassava planting material certification and breeding support - Leiva, Ana Maria; Jimenez, Jenyfer; Gil Ordoñez, Alejandra; Pardo, Juan Manuel; Cuellar, Wilmer Jose (2025)
Cassava Frogskin Disease (CFSD), first reported in Colombia in the 1970s, remains one of the most damaging diseases of cassava, with yield losses exceeding 90% during major outbreaks (Pineda et al., 1983). CFSD affects storage roots, reducing starch accumulation and causing fissures and brittleness, while aerial symptoms are usually absent (Pardo et al., 2022). The disease has also been reported in Costa Rica, Venezuela, Brazil, and Paraguay (Cardozo et al., 2016; de Oliveira et al., 2014; de Souza et al., 2014; Alvarez et al., 2014). Advances in molecular diagnostics have revealed that CFSD is associated with multiple pathogens. To date, four viruses Cassava frogskin associated virus (CsFSaV), Cassava new alphaflexivirus (CsNAV), Cassava polero like virus (CsPLV), and Cassava torrado like virus (CsTLV) as well as 16SrIII phytoplasma have been detected in symptomatic plants (Calvert et al., 2008; Carvajal-Yepes et al., 2014; de Oliveira et al., 2020; Alvarez et al., 2009). Mixed infections are common in vegetatively propagated crops, complicating efforts to identify the specific causal agent (Thomas Sharma et al., 2017). However, recent evidence strongly implicates CsTLV as the primary causal agent, as single infections of this virus are sufficient to reproduce the characteristic root symptoms (Jiménez et al., 2024). Cassava Witches Broom Disease (CWBD) is another significant constraint in cassava growing regions. It causes shoot proliferation, shortened internodes, and reduced root development. CWBD is associated with Ceratobasidium Theobromae (syn. Oncobasidium theobrome, Ceratobasidium theobromae, Thanatephorus theobromae, Rhizoctonia theobromae) (Leiva et al., 2023). This fungus is a wind borne, vascular-restricted, fastidious basidiomycete that was first associated with vascular streak dieback (VSD) of cacao in 1971 (Talbot and Keane, 1971). Despite the availability of enough genetic information for both pathogens, the large-scale evaluation of molecular detection tools for CsTLV species 2 and C theobromae is necessary. For CsTLV-2, the RNA-dependent RNA polymerase (RdRp) gene is the established species demarcation region for torradoviruses, making it an appropriate and informative target for future molecular and epidemiological diagnostics. For C. theobromae, the existing diagnostic method has proven reliable in a recent study done in Laos in cassava genotype; however, certain methodological aspects still require refinement. In both cases, adherence to the guidelines of the European and Mediterranean Plant Protection Organization (EPPO, 2025) is essential to ensure appropriate standardization, validation, and long-term reliability of primers used in molecular diagnostic assays. Such optimization is necessary to guarantee consistent performance under routine diagnostic conditions and to enable the formal incorporation of these assays into clean seed certification programs.